Phonerilins A–K, cytotoxic ingenane and ingol diterpenoids from Euphorbia neriifolia. (24th September 2022) - Gao, Yuan; Zhou, Jun-Su; Liu, Hong-Chun; Zhang, Yan; Yin, Wei-Hang; Liu, Qun-Fang; Wang, Guan-Wu; Zhao, Jin-Xin; Yue, Jian-Min
Abstract: A phytochemical study of the aerial parts of Euphorbia neriifolia led to the isolation of six new ingenane-type diterpenoids, phonerilins A–F (1 –6 ), five new ingol-type diterpenoids, phonerilins G–K (7 –11 ), and five known analogues (12 –16 ). Their structures with absolute configurations were elucidated by a combined method. Phonerilin A (1 ) is the second rearranged ingenane diterpenoid with a unique 6/6/7/3-fused ring system. Based on single-crystal X-ray diffraction and NOESY data, the structure of 20-deoxy-16-hydroxyingenol was revised as 20-deoxy-17-hydroxyingenol (12 ) that is likely the biogenetic precursor of 1 . Biological evaluation revealed some isolates exhibited cytotoxic effects against two human tumor cell lines, A549 and HL-60. Graphical abstract: Image 1